Commentary: Connecting Müller's Philosophical Position-Taking Theory of Emotional Feelings to Mechanistic Emotion Theories in Psychology. (October 2022) - Moors, Agnes
Müller proposes a position-taking theory to account for the manifest image of emotional feelings as "feelings towards". He reduces the process of position-taking to goal-based construal, which is akin to the stimulus-goal comparison process central in appraisal theories. Although this reduction can account for the heat of emotional feelings and the intuition that non-linguistic organisms can also have feelings, it may fail to keep the position-taking aspect on board. Moreover, the image of emotional feelings as active position-takings may itself be questioned and replaced with a passive image. I end by acknowledging that a passive image is still compatible with an active underlying mechanism as is the case in appraisal theories but even more so in the goal-directed theory.